Role of Cryopreservation in Determining Component Composition and Immune Reactivity of Bone Marrow - Matsevitaya, I. Yu.; Ostankov, M. V.; Goltsev, A. N. (Problems of Cryobiology and Cryomedicine, 2006)
The data, characterising GVHR development after transplantation of allogenic bone marrow, modified by component composition, are shown. Certain conditions of bone marrow cryopreservation were demonstrated as enabling to decrease a myelotransplant’s immune reactivity due to inhibiting accessory-regulatory elements function and as a result GVHR manifestation rate by increasing its protective potential.